2002
DOI: 10.1021/la026273k
|View full text |Cite
|
Sign up to set email alerts
|

Probing Microbial Cell Surface Charges by Atomic Force Microscopy

Abstract: Most microorganisms possess a negative surface charge under physiological conditions due to the presence of anionic carboxyl and phosphate groups. Cell surface charge plays an important role in controlling cell adhesion and aggregation phenomena, as well as antigen−antibody, cell−virus, cell−drug, and cell−ions interactions. We have used atomic force microscopy (AFM) with chemically functionalized probes to investigate the surface charges of yeast cells. Force−distance curves and adhesion maps recorded with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(113 citation statements)
references
References 24 publications
6
107
0
Order By: Relevance
“…Under physiological conditions, S. cerevisiae cells have a negatively charged cell surface (35), where surface macromolecules, such as mannoproteins and glucan that contain phosphodiester, amino, and carboxyl groups, produce charge on the cell that aids in adhesion processes (36). Yeast cells can therefore be immobilized on glass supports that have been pretreated with poly(L-lysine).…”
Section: Resultsmentioning
confidence: 99%
“…Under physiological conditions, S. cerevisiae cells have a negatively charged cell surface (35), where surface macromolecules, such as mannoproteins and glucan that contain phosphodiester, amino, and carboxyl groups, produce charge on the cell that aids in adhesion processes (36). Yeast cells can therefore be immobilized on glass supports that have been pretreated with poly(L-lysine).…”
Section: Resultsmentioning
confidence: 99%
“…carboxyl and phosphate) in their membranes (Gilbert et al 1991;Lerebour et al 2004;Palmer et al 2007). However, the magnitude of the charge varies from species to species and can be influenced by various conditions, namely age of the culture, ionic strength and pH (Ahimou et al 2002;Palmer et al 2007). Zeta potential measurements demonstrated that after ITCs exposure, the cells become less negatively charged.…”
Section: Discussionmentioning
confidence: 99%
“…The density of the thiols or disulfides on the gold surface is well determined, and as a result forces between defined chemical groups can be measured [120]. Various rest groups have been used such as carboxyl (-COOH) [121], hydroxyl (-OH) [122], methyl (-CH 3 ), acetate (-OCOCH 3 ) [123,124], amide [125], and amino [126,127]. One problem of chemically modified tips is that they might be destroyed by the interaction with another surface.…”
Section: Modificationmentioning
confidence: 99%
“…A way of measuring the force between two surfaces with a well-defined density of functional groups is to coat the tip with thiols or disulfides. Titration experiments have been done with a number of differently coated surfaces [121,122,[124][125][126][127].…”
Section: Electrostatic Double-layer Force and Dlvo Theorymentioning
confidence: 99%